Pengaruh Motivasi dan Fasilitas Terhadap Peningkatan Keterampilan Peserta Pelatihan di BIPTAK DISPERINDAG Jawa Tengah - Elis Sugeng Pratiwi (Universitas Kristen Indonesia Toraja, 2023)
The purpose of this study was to determine the effect of motivation and facilities on skills. This form of research is quantitative research with a survey approach. Sampling using purposive sampling technique. The research data was obtained by distributing 100 questionnaires to respondents, about the Effect of Motivation and Facilities on Skills. Based on the results of statistical testing, it can be clearly seen that partially (individually) all independent variables affect the dependent variable. The influence given by the two independent variables is positive, meaning that the higher the influence of motivation and facilities, the higher the skills of trainees at BIPTAK Central Java.